La edición universitaria argentina a dos voces: Rafael Centeno y Mónica Aguilar, editores de la Universidad Nacional de Quilmes (Argentina) - Guerra González, Jenny Teresita (2013)
This interview to Rafael Centeno andMónica Aguilar, both editors of theUniversidad de Quilmes, Argentina,Editorial Programme, was done withthe aim to shed light in a general wayon how the scholarly publishing workin Argentina, a country that, along withBrazil and México is at the head of thebook production in Latin America. Theinformation gathered present the in depthsof the editorial catalog, the use of CIT inthe editorial and commercial processes aswell as about the institutional policies of theuniversity and the inter-institucional cooperation,among other issues of interest.